In the Eye of the Beholder: Challenge and Hindrance Appraisals of Work Characteristics and Their Implications for Employee’s Well-Being - Li, Peikai; Peeters, Maria C. W.; Taris, Toon W.; Zhang, Yejun (Frontiers in Psychology, 2021)
Previous research on the association between job characteristics and employee well-being has returned mixed results. In particular, the possible impact of individual appraisal of these job characteristics has not been well-acknowledged. To address this limitation, we drew on appraisal theory and examined (a) how workers appraise particular job characteristics, and (b) how these appraisals affect the relationships between these job characteristics and well-being (i.e., work engagement and burnout). We tested our hypotheses across two studies. In a cross-occupation sample (Study 1, n = 514), we found that job demands and resources can be appraised as both challenges and hindrances. In addition, challenge appraisals can mitigate the detrimental impact of job demands on engagement and burnout; and hindrance appraisals can strengthen the detrimental effects of job demands on burnout. Further, hindrance appraisals of job resources reduce their beneficial effects on engagement and burnout. Study 2 (n = 316 nurses in a hospital) further showed that challenge appraisals of job demands can reduce their impact on burnout while challenge appraisals of job resources will strengthen their positive effect on employee engagement and burnout. We discuss study implications as well as future research directions.